Eco-packaging and fresh food products. Analysis of demand and consumer behavior in Italy - Marzia Ingrassia; Claudio Bellia; Rosaria Disclafani; Pietro Chinnici; Stefania Chironi (Economia Agro-Alimentare)
This paper presents the first results of marketing studies for the positioning of a new sustainable biobased plastic packaging for fresh food, as part of the research project “CItrus waste ReciCLing for added valuE products – CIRCLE” for improving the sustainability of the citrus processing production chain through the valorization of processing waste. The present study, conducted on Italian consumers, contributes to the flow of literature on consumer demand of sustainable food packaging, highlighting the preferences, concerns, and skepticism, the factors that explain behaviors, and the role of information on their choices. Findings may be of interest for firms and Public Institutions to promote circularity behaviors among citizens and to consolidate their ethical motivations through correct information and experience.